IMPLEMENTASI STRATEGI PEMASARAN PENDIDIKAN - Setyaningsih, Rini; Andriani, Rita; Irawati (STKIP Pesisir Selatan, 2023)
This research investigated about the implementation of marketing strategy at Junior High School of Al-Faruqi Kampar. The research problems were 1) how the implementation of marketing strategy was, 2) what supporting and obstructing factors influencing in increasing marketing strategy at Junior High School of Al-Faruqi Kampar. It was a descriptive qualitative research. The main informants of this research were the principal and the vice of public relations, and the supporting informants were 1 head of school administration, 1 HRD (human resource development) team, 5 guardians of students and 4 students. The object of this research was the implementation of marketing strategy at Junior High School of Al-Faruqi Kampar. Observation, interview, and documentation were used for collecting the data. The data were analyzed by using reduction, presentation, and conclusion. The findings of this research showed that the implementation of marketing strategy at Junior High School of Al-Faruqi Kampar was in accordance with the proper way: planning a marketing strategy by using market identification, segmentation, product differentiation, marketing communications and educational institutions properly services. The obstructing factors in implementing of marketing strategies at Junior High School of Al-Faruqi Kampar were the permission when entering the promotion permit, there were schools that did not accept it. The Supporting factors in implementing of marketing strategies at Junior High School of Al-Faruqi Kampar were using relationships, the relationships were the parents of students and students to help promote.